The Corporate Governance Characteristics versus Capital Structure of Portuguese Companies - Santos de Oliveira, Helena Maria (2022)
This study analyzes the relationship between Corporate Governance and the level of leverage of Portuguese companies. The sample consists in 9,170 Portuguese non-financial companies corresponding to 100,870 observations, over a period from 2008 to 2018. The data for this study were collected by consulting the SABI database and were analyzed using random effects regression models, considering the data model in panel, by using the integrated development software program for R – RStudio, version 1.2.5001. The analysis of the results provides evidence that Corporate Governance influence the choice of capital structure of Portuguese companies.